Experimental Musical Instruments: Early Years. Selection from the first seven years of the Experimental Musical Instruments annual audio cassette series, 1985-1992 (Point Reyes Station Windworld, 2000)
Early Years is the first of a pair of CDs containing selections from the Experimental Musical Instruments annual audio cassette series that ran from 1985 - 1999. (The other CD, called Later Years, is described here.) Each CD includes a sixteen-page booklet containing the original notes followed by short updates on most of the artists and their work. The master tapes have been digitally remastered, and the sound quality on the CDs is better than that of the original cassettes.You can buy either of the CDs separately for $14.00, or the pair for $24.Complete contents as well as audio samples for the Early Years CD can be found below. But first, here are teasers for a few of the selections:The Baschet Cristal is the most refined of the extraordinary glass-and-steel instruments created by the Brothers Baschet in France. On the CD, a trio of Cristals are featured in a composition called "Valse" by the French composer Daniel Ouzounoff.In his piece "47 Whale Raga," Jim Nollman plays guitar through a specially designed underwater speaker system while sailing among a pod of whales. The whales answer the guitar sounds, call-and-response style, with choruses of their own.Vera Meyer plays a glass harmonica made by the late Gerhard Finkenbeiner, who until his recent death was the leading modern maker of the instrument.The strangely bent reverberances of the Waterphone can be heard in the hands of the instrument's maker in Richard Waters' "Noncomposition for Three Waterphones."Warren Burt and Ernie Althoff play a floatingly sustained and otherworldly "Improvisation in an Ancient Greek Mode" on a set of justly tuned, hand-held tuning forks.In "Improvisations for Feedback," David Myers plays the Feedback Machine - a network of digital delays that bounce anomalous electronic sound-artifacts back and forth among themselves to generate the most improbable rhythmic and textural music.~~~~~~~~~~~~~~~~~~~~~~~~~~~~COMPLETE LIST OF MUSICIANS, SONG TITLES AND INSTRUMENTS FEATURED ON EXPERIMENTAL MUSICALINSTRUMENTS -- EARLY YEARS:The Glass Orchestra: "Believe It Or Not." All glass instrumentsBil King: "Midnight Sonata" and "Just Kidding." The BoardTUYO: excerpts from Masque and Gamelan. Percussion tubes, tuned shakers, modified accordions and moreJim Nollman: "47 Whale Raga." Underwater guitar, accompanied by whalesThe Boneworks Ensemble: "Ark." Instruments of boneThe Lasry-Baschet Ensemble: "Valse." The Baschet CristalsWarren Burt and Ernie Althoff: "Improvisation in an Ancient Greek Mode." Tuning forksWee Jimmie Scott: "The Barren Rocks of Adden." Abraham's Goliath Rock DulcimerRichard Waters: "Non-Composition for Three Waterphones." Waterphones (musical excerpt below)David Myers: "Improvisations for Feedback." The Feedback MachineMusic for Homemade Instruments: excerpts from Glyptodont. Instruments from throwawaysVera Meyer: Johann Gottlieb Naumann's "Sonata." Glass harmonicaHans Reichel: "Thinking." Pick-Behind-The-Bridge GuitarWilliam Eaton: "Magical-Musical Duet." 26-String guitar and lyrichordJohn Hajeski: "The Dentist." Portable AnarchyMinnie Black: "The Monkey Song." The Gourd Ola (musical excerpt below)Rick Sanford: "Time and Time Again" (1989). The Sink (musical excerpt below)Dudley Duncan: "Cosmic Koto." The Cosmic KotoRobin Goodfellow & friends: "Five Short Improvisations." Balloons, egg shells, soda straws and other homemades (musical excerpt below, featuring the seaweed flute Robin calls Mal de Meer
Keywords: 20th Century (1901-2000)